Important Topics in Teaching English to Engineering Students in Uzbekistan - Ruzikulova Gulirukhsor Gofur kizi; Ganiyev Elbek (Zien Journals, 2022)
Due to the great attention paid to language learning in the Republic of Uzbekistan, now almost every educational institution pays special attention to the study and teaching of foreign languages. In teaching EFL teachers should pay attention to choose proper teaching methods in order to make their lessons clear and effective for the learners. When teaching English to non-philological students in engineering, it is important to choose topics that are common to all.
Keywords: ESP; engineer; engineering; mechanic